Bridging the Gap: Social Networks and Professional Development in the Eyes of Prospective Science Teachers - Khaleel Alarabi; Suzan Al Abidi; Linda S. Pagani; Hassan Tairab; Younis Alhosani; Lutfieh Rabbani; Maitha Al Mansoori (Ital Publication, 2024)
Virtual social network platforms have rapidly become settings for cultivating various types of bonding, bridging, and building social capital. This promotes professional and personal relationships and has implications for our psychological wellness. Our qualitative study, which has taken place in the United Arab Emirates (UAE) and Oman, explored the perspectives of science teachers in training regarding the utilization of social networks for professional development (PD). We conducted 26 semi-structured interviews across both countries. Our results unveiled nuanced insights into the influence of social networks on the professional development of prospective science teachers, the challenges they face while using these means for networking, and how cultural norms and institutional factors impact learning, collaboration, and adoption of such virtual social systems. The findings suggest that social networks can serve as valuable tools for the professional development of prospective science teachers. Notably, there was a subtle divergence between the two groups. The UAE participants have emphasized global perspectives and valued insights into worldwide educational trends, whereas the Omani participants have appreciated the global perspective and prioritized local connections. Additionally, remarkable differences in technology access and infrastructure challenges between UAE and Oman teachers in training highlight the need for more equitable professional development opportunities. Emirati and Omani participants differ in their access to international educational trends and technology because of economic disparities. This could be translated into more resources for education and technological infrastructure, as the geographical location of the UAE as a global hub makes it easier to access global networks and trends. The implications of these findings point to the critical need for the effective use of social networks in the professional development of science teachers. Doi: 10.28991/ESJ-2024-08-01-014 Full Text: PDF